A Comparative Study of Multidetector Computed Tomography, Cone Beam Computed Tomography, and Computed Microtomography on Trabecular Bone Structures in the Human Mandible: An Ex Vivo Study. Issue 4 (July 2021) - Sarmento, Viviane Almeida; de Oliveira Gonzalez, Thais Feitosa Leitão; Lopes, Ricardo Tadeu; Novaes, Marco; Borges, Sirlene Mendes; Rubira-Bullen, Izabel Regina Fischer
Abstract : Objective: The aim of this study was to evaluate the accuracy of multislice computed tomography (MSCT) and cone beam computed tomography (CBCT) scanners in the assessment of trabecular bone microarchitecture by radiomorphometric analysis. Methods: Eight dry human hemimandibles were selected and scanned by 4- and 128-MSCT, CBCT with different voxel sizes, and a computed microtomography (micro-CT). The images were spatially aligned, the axial slices were segmented using CTAn software (Skyscan, Konitch, Belgium), and 10 bone morphometric parameters were quantified. The micro-CT images were the criterion standard. Results: The results show the superiority of CBCT images with 0.2-mm voxel size and 128-MSCT. Conclusions: We can conclude that the CBCT scanner with 0.2-mm voxel size and 128-MSCT had better performance on reproducibility of the distribution and organization of trabecular bone and marrow spaces evaluated in this study.